Remediation of boron, lithium, and molybdenum by date pits modified with graphene oxide and cellulose nanocrystals: Mechanistic studies - Dana A. Da'na (17019120) (2023)
This work aimed to modify date pits (DP), an agricultural waste product, with graphene oxide (GO) and cellulose nanocrystals (CNC) to develop a novel, environmentally friendly adsorbent referred to as GO-CNC@DP. A comprehensive study of the physicochemical characteristics of the prepared adsorbent in addition to the batch adsorption investigation on multiple pollutants (boron, lithium, and molybdenum) was studied. The results concluded that the endothermicity of the process due to the positive value of enthalpy change ΔH° that favors low levels of disorder and is spontaneous in nature due to the negative ΔG° values. At pH 2, the maximum adsorption capacities ranged between 15.5 mg/g and 82 mg/g for the three studied pollutants. The increase in adsorption capacity can be attributed to the alteration of the initial temperature from 25 °C to 45 °C. This phenomenon can be elucidated by considering the interactions such as surface complexation, electrostatic attraction, and ion exchange that occur between the pollutant and the adsorbent's surface. The excellent adsorption of boron, lithium, and molybdenum can be attributed to the attachment of GO to CNC on DP, which not only added more adsorption sites but also partially inhibited the aggregation of CNC. Therefore, GO-CNC@DP exhibited great results in the remediation of boron, lithium, and molybdenum from water in comparison to DP. Other Information Published in: Groundwater for Sustainable Development License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.gsd.2023.101008